Neural correlates of own and close-other’s name recognition: ERP evidence - Tacikowski, Pawel; Cygan, Hanna B.; Nowicka, Anna (Frontiers in Human Neuroscience, 2014)
One’s own name seems to have a special status in the processing of incoming information. In event-related potential (ERP) studies this preferential status has mainly been associated with higher P300 to one’s own name than to other names. Some studies showed preferential responses to own name even for earlier ERP components. However, instead of just being self-specific, these effects could be related to the processing of any highly relevant and/or frequently encountered stimuli. If this is the case: (1) processing of other highly relevant and highly familiar names (e.g., names of friends, partners, siblings, etc.) should be associated with similar ERP responses as processing of one's own name; and (2) processing of own and close others' names should result in larger amplitudes of early and late ERP components than processing of less relevant and less familiar names (e.g., names of famous people, names of strangers, etc.). To test this hypothesis we measured and analyzed ERPs from 62 scalp electrodes in 22 subjects. Subjects performed a speeded two-choice recognition task - familiar vs. unfamiliar - with one’s own name being treated as one of the familiar names. All stimuli were presented visually. We found that amplitudes of P200, N250 and P300 did not differ between one’s own and close-other’s names. Crucially, they were significantly larger to own and close-other’s names than to other names (unknown and famous for P300 and unknown for P200 and N250). Our findings suggest that preferential processing of one’s own name is due to its personal-relevance and/or familiarity factors. This pattern of results speaks for a common preference in processing of different kinds of socially relevant stimuli.